Endothelin receptor antagonists (ERAs) can potentially be used as therapeutic drugs to reduce hypertension caused by small molecule tyrosine kinase inhibitors (TKIs) - He, Qingjian; Lin, Junling; Mo, Chanjuan; Li, Guodong; Lu, Jianzhong; Sun, Qiyin; Cao, Lijun; Gan, Haojian; Sun, Quan; Yao, Jiafang; Lian, Shengyi; Wang, WenJuan (Frontiers in Pharmacology, 2025)
The emergence of targeted anti-tumor drugs has significantly prolonged the lifespan and improved the prognosis of cancer patients. Among these drugs, vascular endothelial growth factor (VEGF) inhibitors, particularly novel small molecule tyrosine kinase inhibitors (TKIs), are extensively employed as VEGF inhibitors; however, they are also associated with a higher incidence of complications, with hypertension being the most prevalent cardiovascular toxic side effect. Currently, it is widely accepted that TKIs-induced hypertension involves multiple mechanisms including dysregulation of the endothelin (ET) axis, reduced bioavailability of nitric oxide (NO), imbalance in NO-ROS equilibrium system, vascular rarefaction, and activation of epithelial sodium calcium channels; nevertheless, excessive activation of ET system appears to be predominantly responsible for this condition. Moreover, studies have demonstrated that ET plays a pivotal role in driving TKIs-induced hypertension. Therefore, this review aims to explore the significance of ET in the pathogenesis of hypertension induced by targeted anti-tumor drugs and investigate the potential therapeutic value of endothelin antagonists in managing hypertension caused by targeted anti-tumor drugs.